Diagnostic and Therapeutic Strategies for Peritoneal Tuberculosis: A Review - Wu, David C. (J Clin Transl Hepatol, 2019)
Peritoneal tuberculosis (PTB), although rarer than its pulmonary counterpart, is a serious health concern in regions of the world with high tuberculosis prevalence. Individuals with baseline immunocompromise condition, whether acquired or medically induced, are at greatest risk for experiencing PTB. While medical treatment of the condition is similar to that of the pulmonary disease, the generally immunocompromised state of those infected with PTB, along with a lack of highly sensitive and specific testing methods make early diagnosis difficult. This review discusses the risks factors, clinical features, diagnostic methods, and treatment options for PTB.